P.097 After-discharges and presurgical cortical stimulation in stereo-encephalography in the study of drug-resistant epilepsy. (June 2022) - Asim, A; McShane, M; Paredes-Aragón, EM; Mirsattari, SM
Abstract : Background: Background: Cortical stimulation (CS) as a part of presurgical investigations in patients undergoing implantation of depth electrodes (SEEG) is a growing practice in some Comprehensive Epilepsy Centers. After-discharges (AD) are useful to determine epileptogenic tissue within or outside the epileptogenic network. Classification of afterdischarges was proposed by Blume using subdural recordings(1); its utility in SEEG is unknown. Methods: Methods: Single center, retrospective study that included patients with SEEG that underwent CS in the Epilepsy Monitoring Unit. Demographic characteristics were explored and Blume's proposed AD classification was used to determine whether or not the CS changed surgical outcomes. Results: Results: From January 2015 to June 2021, a total of 177 patients were implanted with SEEG and analyzed. 95 patients had CS and 91 had AD. Morphologies found were: Rhythmic waves in 4 (0.04%), Rhythmic waves evolving into spikes in18 (19%), Polyspike bursts in 14 (15%), Spike-waves in 28 (30%), and sequential spikes in 18 (19%). 12/14 (86%) patients with Spike-waves had Engel I outcome; Engel class IV patients were more likely to have an evolution of morphology and frequency of ADs in 3 patients(75%). Conclusions: Conclusions: The most frequent morphology of ADs seen was spike-waves. AD morphology and duration may predict post-operative seizure outcomes.